NEW AND REVISED TOURNAISIAN (EARLY MISSISSIPPIAN)FORAMINIFERAL TAXA FROM BELGIUM (Rivista italiana di Paleontologia e Stratigrafia, 2005)
Hastarian formations in southern Belgium contain previously undescribed or unfigured foraminiferal  taxa that provide a link to better known early Tournaisian faunas from eastern Europe.  Characteristic specimens are illustrated, and selected elements are formally described as part of continuing research to reorganize Belgian Mississippian foraminiferal zones. Taxonomic discussions  include description of the new genus Crassiseptella, emendation of the genera Spinochernella and Condrustella and reevaluation of the genus Granuliferelloides.